Enhancing the Texture and Sensory Properties of Pickled Cucumbers with Different Brine Solutions - Mahdieh Yousefi; Akram Arianfar; Vahid Hakimzadeh; Ali Rafe (Foods)
Softening of pickled cucumbers during storage poses significant challenges for the pickle industry, leading to considerable losses. This softening is attributed to the breakdown of pectic materials in the middle lamella of the cucumber tissue. To address this issue, our study aimed to assess the impact of various ions on cucumber pickle fermentation, storage (over 6 months), as well as overall structure and texture. Fermentation brines were prepared, incorporating different salts, such as KCl, CaCl2, MgCl2, AlCl3, and calcium acetate, at concentrations of 50, 100, 200, and 400 ppm, alongside 6% NaCl. Each month, we removed the pickles from the fermentation brines and analyzed their physicochemical and sensory properties. Our findings revealed that, when pH declined to 3.6, undesirable textural and sensory properties were observed in the pickled cucumbers. However, pickles treated with CaCl2 and calcium acetate exhibited higher pH levels compared to other samples after 6 months. Calcium ions demonstrated a positive effect on firmness, contributing to improved consumer acceptance during storage. Among the different salts tested, firmness followed the order of Ca(C2H3O2)2 > CaCl2 > KCl > MgCl2 > AlCl3. Furthermore, we observed a positive relationship between pickle firmness and crispness, as well as color values. The sensory evaluation affirmed the positive influence of Ca2+ on enhancing pickles’ firmness throughout their shelf-lives. Ca-acetate and CaCl2 displayed the most favorable results across sensory, textural, and physical properties among the samples. In conclusion, the addition of Ca-acetate in conjunction with CaCl2 was proven to be an effective approach in improving the firmness and extending the shelf-life of cucumber pickles. Our study highlights the potential of calcium ions to enhance the quality and durability of pickled cucumbers, offering promising implications for the pickle industry.